2017
DOI: 10.1002/adma.201606914
|View full text |Cite
|
Sign up to set email alerts
|

LiNbO3:Pr3+: A Multipiezo Material with Simultaneous Piezoelectricity and Sensitive Piezoluminescence

Abstract: Red-emitting piezoluminescence (elasticoluminescence) is achieved by doping rare earth Pr into the well-known piezoelectric matrix, LiNbO . By precisely tuning the Li/Nb ratio in nonstoichiometric Li NbO :Pr , a material that exhibits an unusually high piezoluminescence intensity, which far exceeds that of any well-known piezoelectric material, is produced. Li NbO :Pr shows excellent strain sensitivity at the lowest strain level, with no threshold for stress sensing. These multipiezo properties of sensitive pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
146
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(157 citation statements)
references
References 23 publications
5
146
0
Order By: Relevance
“…In terms of the selection of oxide dielectric materials, LiNbO 3 (LNO) has attracted great research interest in the past two decades, because of its multifunctional properties including ferroelectric, piezoelectric, pyroelectric, electro‐optics, acousto‐optical, birefringence, and nonlinear optical properties . LNO also presents enormous potentials in optical devices, such as electro‐optical and acousto‐optical modulators, actuators, second‐harmonic generators, and waveguides .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the selection of oxide dielectric materials, LiNbO 3 (LNO) has attracted great research interest in the past two decades, because of its multifunctional properties including ferroelectric, piezoelectric, pyroelectric, electro‐optics, acousto‐optical, birefringence, and nonlinear optical properties . LNO also presents enormous potentials in optical devices, such as electro‐optical and acousto‐optical modulators, actuators, second‐harmonic generators, and waveguides .…”
Section: Introductionmentioning
confidence: 99%
“…Mater. [203] They coated the material over the surface of an aluminum alloy plate, and applied the tensile strain onto the plate. 2019, 4, 1800626 leading groups in this field, developed SrAl 2 O 4 :Eu piezoluminescence material embedded in an epoxy resin (a polymeric system), and found that this resin can be used for a nondestructive evaluation method for detecting a crack produced in metals.…”
Section: Wwwadvmattechnoldementioning
confidence: 99%
“…[202] Furthermore, in 2017, the group presented an efficient, thresholdless red-emitting piezoluminescence system where Pr 3 + was doped into the well-known piezoelectric matrix, LiNbO 3 , and demonstrated the stress-sensing performance of this system for practical use in industry. [203] They coated the material over the surface of an aluminum alloy plate, and applied the tensile strain onto the plate. As a result, this material repeatedly exhibited continuous mechanoluminescence with the strain change, and the luminescence intensity was tuned even with very low strain (≈1 × 10 −4 % strain).…”
Section: Wwwadvmattechnoldementioning
confidence: 99%
“…For the paint film sensor, the elastic module is ≈ 1 GPa, and according to Hooke's law, a strain sensitivity of 1 µST is equivalent to a stress sensitivity of 1 kPa and it means that this paint film would be suitable as an excellent microforce sensor for piconewton‐scale precision tests (at a 1 × 1 µm area). This would greatly improve the dynamic range and accuracy of ML detection, particularly beneficial to the development of bioimaging with single‐cell resolution, and the sensing and control in microrobotic cell manipulation . It should be noted that all the measurements for quantitative evaluations are carried out under the standardized condition (i.e., the irradiation and waiting times of 60 and 300 s, respectively) explained in detail in the Experimental Section.…”
Section: Scalable Elasticoluminescent Strain Sensormentioning
confidence: 99%